Polemik Otoritas Hadis: Kontribusi Aisha Y. Musa dalam Peneguhan Hadis Sebagai Kitab Suci - Ahmadi, Rizqa; Hefni, Wildani (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2020)
The polemic of hadith authority seems to be endlessly debated by Western and Eastern scholars, Muslims as well as non-Muslims. Aisha Y. Musa reconstructed the debate and discourse of the authority of prophetic traditions by looking at the early manuscripts of the hadith experts. Musa also presented the narratives of the opposition of hadith in the digital era. This debate shows that the authority of hadith did not always enjoy such widespread acceptance. Opposition to the hadith has emerged among Muslims from the first century and has not been limited to one era only, but until now in our contemporary digital era. The polemics are, however, not influenced by Western scholarship and orientalists. On the contrary, it is more response from Muslims to the elevation of the hadith along with the Qur’an as the duality of revelation.